Kewarganegaraan Ganda dalam Perspektif Hukum Islam dan Hukum Internasional: Tantangan dan Solusi: Dual Citizenship in the Perspective of Islamic Law and International Law: Challenges and Solutions - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Azzahra Sindhi Latifa; Roihatul Jannah; Defita Diah Ayu (LITERA: Jurnal Ilmiah Mutidisiplin, 2024)
Dual nationality is a growing phenomenon in the era of globalization, but it presents various challenges from both Islamic law and international law perspectives. In Islamic law, dual nationality is not explicity addressed; however, principles such as the unity of the ummah (community) and obligations toward the state can create dilemmas concerning dual obligations, such as taxes or military service. Islam teaches compliance with laws that do not contradict Sharia, but dual nationality can lead to conflicts between duties toward the state and religious obligations. Meanwhile, in international law, dual nationality often raises issues related to state sovereignty, dual obligations, and legal conflicts between countries. Countries that permit dual nationality face difficulties in terms of diplomatic protection and the regulation of individual rights. Possible solutions include international negotiations, the adoption of more flexible dual nationality policies, and increasing legal awareness for individuals involved. This paper aims to explore the challenges faced by individuals with dual nationality in the context of Islamic law and propose pratical solutions to address these issues.